Hospital-based registries of women with breast cancer from the oncology network of Espírito Santo, Brazil - Pessanha, Raphael Manhães; Grippa, Wesley Rocha; Lopes-Júnior, Luís Carlos (Revista de Enfermagem da UFPI, 2024)
Objective: To describe the cases of women with breast cancer (BC) and identify the epidemiological profile of the cases reported in the Hospital-based Cancer Registries (HCR) of the Oncological Care Network of Espírito Santo (OCN/ES). Methods: This is a hospital-based descriptive observational study, based on secondary data retrieved via the HCR Tumor Registration Form of the eight hospitals that comprising the OCN/ES, between 2000-2020. Results: There were 16,844 case records of women with breast cancer in this historical series. The median age of the women was 52 years. The age group with the highest number of cases (54.0%) was 41-60 years, 57.42% were brown, 51.70% married, and 30.80% had incomplete elementary school, residents of the Metropolitan region of the state (81.70%). Most cases were analytical (75.42%), referred from SUS (59.70%), had no occurrence of more than one primary tumor (94.21%), the most common histological type was infiltrating duct carcinoma (76.03%), and stage II (6.75%), with multimodal treatments (60.09%). Conclusion: The findings point to an increasing trend in the occurrence of breast cancer over the years in OCN/ES, occurring mainly in older, brown women and women with low education, in stage II of the disease.